(دور التربية الإسلامية في الإنماء الخلقي للشعب (دراسة على الإسلام ودوره في الإنماء القومي بإندونيسيا - Tabrani ZA (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
Islam as a religion of rahmatan li al'alamin, very much its contribution to the national development which is oriented to the whole human development. The presence of religion is always accompanied by